Reprint of Pharmacological and molecular characterization of the positive allosteric modulators of metabotropic glutamate receptor 2. (15th March 2017) - Lundström, L.; Bissantz, C.; Beck, J.; Dellenbach, M.; Woltering, T.J.; Wichmann, J.; Gatti, S.
Abstract: The metabotropic glutamate receptor 2 (mGlu2 ) plays an important role in the presynaptic control of glutamate release and several mGlu2 positive allosteric modulators (PAMs) have been under assessment for their potential as antipsychotics. The binding mode of mGlu2 PAMs is better characterized in functional terms while few data are available on the relationship between allosteric and orthosteric binding sites. Pharmacological studies characterizing binding and effects of two different chemical series of mGlu2 PAMs are therefore carried out here using the radiolabeled mGlu2 agonist 3 [H]-LY354740 and mGlu2 PAM 3 [H]-2, 2, 2-TEMPS. A multidimensional approach to the PAM mechanism of action shows that mGlu2 PAMs increase the affinity of 3 [H]-LY354740 for the orthosteric site of mGlu2 as well as the number of 3 [H]-LY354740 binding sites. 3 [H]-2, 2, 2-TEMPS binding is also enhanced by the presence of LY354740. New residues in the allosteric rat mGlu2 binding pocket are identified to be crucial for the PAMs ligand binding, among these Tyr 3.40 and Asn 5.46 . Also of remark, in the described experimental conditions S731A (Ser 5.42 ) residue is important only for the mGlu2 PAM LY487379 and not for the compound PAM-1: an example of the structural differences among these mGlu2 PAMs. This study provides a summary of the information generated in the past decade on mGlu2 PAMs adding a detailed molecular investigation of PAM binding mode. Differences among mGlu2 PAM compounds are discussed as well as the mGlu2 regions interacting with mGlu2 PAM and NAM agents and residues driving mGlu2 PAM selectivity. This article is part of the Special Issue entitled 'Metabotropic Glutamate Receptors, 5 years on'. Highlights: The characterization of the mechanism of action of two MGLU2 PAMs, using both functional and affinity assays, shows the presence of some level of cooperativity between allosteric and orthosteric sites. This large mutagenesis study completes the current understanding of the key residues relevant for positive allosterism. The combination of affinity and functional studies is proposed as a relevant strategy for the definition of the structural changes associated with receptor activation in presence of a positive allosteric modulators.